The pharmacological evaluation of antifertility role of Plumeria acuminata on the reproduction of female Wistar rats - Jay P Rabadia, Tushar R Desai, Vihang S Thite (Journal of Applied Pharmaceutical Science, 2022)
Treatment-induced imbalance in female reproductive hormones can lead to difficulty in ovulation and preparing the endometrium for efficient reception can cumulatively suggest the antifertility role of the drug. Traditionally, ancient herbal medicines are proficiently used to rule out fertility and its control-related issues. This research aims to explore a fertility regulatory profile of leaves and roots ethanolic extract from Plumeria acuminata of the Apocynaceae family. Plumeria acuminata leaves and roots ethanolic extracts were prepared by cold maceration process, subjected to qualitative phytochemical analysis, and acute toxicity test. Based on the LD50 values, 100, 200, and 400 mg/kg doses of both extracts were determined for antifertility activity in adult Wistar female rats. Test-item treatments were given orally from day 1 to 28. Morphological, hematological, hormonal, and histological examinations were performed on day 29 after euthanizing animals. Administration of extracts expressively altered the hormonal intensities up to ~7%–99%, i.e., a decrease in estrogen, progesterone, and luteinizing hormone level as well as an increased in folliclestimulating hormone level. Anatomical alterations in reproductive organs were confirmed by observing cystic follicles and atrophied squamous cells during histopathological evaluation. Vaginal smear evaluation confirmed the disturbance of the estrous cycle with an increase in estrous cycle length up to ~8%–64% as well as a decrease in the number of the estrous cycle and each phase up to ~0%–118% except for diestrus phase. Achieved antifertility results can be attributed to hormonal imbalance, mainly caused by the stigmasterol, saponins, flavonoids, and alkaloids groups of phytochemicals in leaves and roots ethanolic extracts.
Keywords: Anti-fertility, estrous cycle, estrogen, FSH, LH, histopathology